Masers: Precision probes of molecular gas. Issue 2 (15th January 2020) - Richards, A.M.S.; Sobolev, A.; Baudry, A.; Herpin, F.; Decin, L.; Gray, M.D.; Etoka, S.; Humphreys, E.M.L.; Vlemmings, W.
Abstract: Maser emission from water, methanol, silicon monoxide and other molecules can reach brightness temperatures ≫ 10 10 K. Such observations can achieve sub-pc precision for discs around black holes or sub-au scale interactions in protostellar discs and the regions where evolved star winds reach escape velocity. Ultra-high resolution maser observations also provide photon statistics, for fundamental physics experiments. RadioAstron has shown the success – and limitations – of cm-wave maser observations on scales ≪ 1 mas with sparse baseline coverage. ALMA, APEX and earlier single dish searches have found a wealth of mm and sub-mm masers, some of which probably also attain high brightness temperatures. Masers are ideal for high-resolution observations throughout the radio regime and we need to consider the current lessons for the best observational strategies to meet specific science cases.